Extracting the key electrical properties of semiconductors using optical pump terahertz probe spectroscopy - Johnston, M (IEEE, 2016)
We have used optical-pump-terahertz-probe spectroscopy (OPTPS) to study a range of novel of semiconductors including III-V nanowires and metal halide perovskites. We show that OPTPs allows key figures of merit to be extracted in a non-contact manner, including charge mobility, surface recombination velocity, and doping density. Furthermore, the technique allows charge recombination dynamics to be followed on a picosecond time-scale. This knowledge is useful in the design of new optoelectronic devices from lasers to solar cells as well as for the development and optimisation of new semiconductors.